Physiologically Responsive Polyurethanes for Tissue Repair and Regeneration. Issue 10 (15th August 2022) - Liu, Wenxing; Li, Shifen; Wang, Beiduo; Peng, Pai; Gao, Changyou
Abstract : Polyurethanes have been broadly used as biomaterials in tissue repair and regeneration due to their preeminent biocompatibility and mechanical properties. However, traditional polyurethanes are not able to efficiently cope with the complexity of dynamic tissue microenvironments during the process of disease therapy. Physiologically responsive polyurethanes responding or reacting to biological signals or pathological abnormalities can change their physicochemical properties, enabling on‐demand release or intelligently promoting tissue regeneration. So far, the physiologically responsive polyurethanes have gained significant interest for applications in controlled drug delivery systems and tissue engineering in recent years. This review highlights the research advances in the design of the physiological‐responsive polyurethanes and their applications for tissue repair and regeneration, with particular attention to some representative examples such as pH‐, redox‐, temperature‐, and enzyme‐responsive polyurethanes. The key design principles and applications are illustrated in the treatment of retinal detachment, gastric ulcer, wound, myocardial infarction, lung injury, bone defect, and osteoarthritis. The challenges and future perspectives of the physiological‐responsive polyurethanes are finally discussed. Abstract : Polyurethanes that are sensitive to biological signals or pathological abnormalities can change their physiochemical features to improve therapy efficacy and thus can act as a smart therapeutic platform. This review introduces the fabrication strategies of several physiologically responsive polyurethanes, followed by a discussion of their applications in tissue repair and regeneration.